Self‐Assembly of Immune Signals to Program Innate Immunity through Rational Adjuvant Design. Issue 1 (14th November 2022) - Bookstaver, Michelle L.; Zeng, Qin; Oakes, Robert S.; Kapnick, Senta M.; Saxena, Vikas; Edwards, Camilla; Venkataraman, Nishedhya; Black, Sheneil K.; Zeng, Xiangbin; Froimchuk, Eugene; Gebhardt, Thomas; Bromberg, Jonathan S.; et al.
Abstract: Recent clinical studies show activating multiple innate immune pathways drives robust responses in infection and cancer. Biomaterials offer useful features to deliver multiple cargos, but add translational complexity and intrinsic immune signatures that complicate rational design. Here a modular adjuvant platform is created using self‐assembly to build nanostructured capsules comprised entirely of antigens and multiple classes of toll‐like receptor agonists (TLRas). These assemblies sequester TLR to endolysosomes, allowing programmable control over the relative signaling levels transduced through these receptors. Strikingly, this combinatorial control of innate signaling can generate divergent antigen‐specific responses against a particular antigen. These assemblies drive reorganization of lymph node stroma to a pro‐immune microenvironment, expanding antigen‐specific T cells. Excitingly, assemblies built from antigen and multiple TLRas enhance T cell function and antitumor efficacy compared to ad‐mixed formulations or capsules with a single TLRa. Finally, capsules built from a clinically relevant human melanoma antigen and up to three TLRa classes enable simultaneous control of signal transduction across each pathway. This creates a facile adjuvant design platform to tailor signaling for vaccines and immunotherapies without using carrier components. The modular nature supports precision juxtaposition of antigen with agonists relevant for several innate receptor families, such as toll, STING, NOD, and RIG. Abstract : Self‐assembly of peptide antigen and distinct combinations and ratios of toll‐like receptor agonists into immune polyelectrolyte multilayers reveal activating multiple toll‐like receptor signaling pathways generates distinct types of antigen‐specific response. This strategy can be used to improve vaccine design by initiating a multifaceted immune attack against a singular antigen creating robust antigen‐specific immunity.